Intercalated bacterial biofilms are intrinsic internal components of calcium-based kidney stones - William C. Schmidt; Ava Mousavi; Jiahui Li; Rena Yang; Gerson Gonzalez Marin; Henry L. Schreiber; Rachael E. S. Hammann; Chloe L. P. Obernuefemann; Karla Bergeron; Aleksandra Klim; Daniel Wong; Kefu Du; et al. (Proceedings of the National Academy of Sciences, 2026)
Calcium oxalate stones comprise greater than 70% of all kidney stones. In the current conceptual framework, the initial stone nidus is thought to include the aggregation of inorganic crystallites, the formation of which is favored by elevated concentrations of dissolved constituents. Here, we show that this highly prevalent stone type comprises a form of organic–inorganic polycrystalline biocomposite with integrated bacterial biofilms. Evidence from electron microscopy and fluorescence microscopy reveal the unanticipated internal structure of kidney stones from human patients, where bacterial biofilms are intercalated between polycrystalline mineral layers, even in stones identified as “noninfectious” clinically, including those in patients without underlying urinary tract infections. We observe similar bacterial biofilm architectures on the surfaces of stone fragments obtained due to lithotripsy, suggesting that bacteria are intrinsic to the process of nephrolithiasis. Crystallites proximal to biofilm layers exhibit significantly smaller grain sizes, which indicate a larger local concentration of nucleation sites. Staining reveals that biofilm areas of these stones are enriched with bacterial DNA. That bacteria are now observed so broadly in kidney stones (including even in less prevalent struvite stones) may be conceptually salient: Based on the evidence adduced here, we propose a model in which the urine-rich environment of the kidney can impinge on bacterial calcium homeostasis and amplify bacterial production of nucleation templates such as extracellular DNA. The resultant counterion condensation intrinsic to polyelectrolytes charged beyond the Manning criterion (such as DNA) drastically enhances the probability of heterogeneous nucleation, thereby amplifying calcium oxalate stone formation.